Effect of prolonged exercise in a hypoxic environment on cardiac function and cardiac troponin T. Issue 1 (29th January 2004) - Shave, R E; Dawson, E; Whyte, G; George, K; Gaze, D; Collinson, P
Abstract : Background: Exercise induced cardiac fatigue has recently been observed after prolonged exercise. A moderate to high altitude has been suggested as a possible stimulus in the genesis of such cardiac fatigue. Objective: To investigate if exercise induced cardiac fatigue and or cardiac damage occurs after prolonged exercise in a hypoxic environment. Methods: Eight trained male triathletes volunteered for the study. Each completed two 50 mile cycle trials, randomly assigned from normobaric normoxia and normobaric hypoxia (15% Fio 2 ). Echocardiographic assessment and whole blood collection was completed before, immediately after, and 24 hours after exercise. Left ventricular systolic and diastolic functional variables were calculated, and serum was analysed for cardiac troponin T. Results were analysed using a two way repeated measures analysis of variance, with α set at 0.05. Results: No significant differences were observed in either systolic or diastolic function across time or between trials. Cardiac troponin T was detected in one subject immediately after exercise in the normobaric hypoxic trial. Conclusions: A 50 mile cycle trial in either normobaric normoxia or normobaric hypoxia does not induce exercise induced cardiac fatigue. Some people, however, may exhibit minimal cardiac damage after exercise in normobaric hypoxia. The clinical significance of this is yet to be elucidated.